Settlement of shipworms (Mollusca, Pelycepoda Teredinidae) on mangrove substrates in New Buswang, Kalibo, Aklan. - Pasion, Ma. Tissa Carlamae Villavert
The effects of tidal level and water movement were studied in a replanted mangrove forest in New Buswang, Kalibo, Aklan. A 10 x 10 m plot was laid in the three tidal zones (low, middle, high). Twelve woods with a length of 1 m were tied and exposed within each plot. Sampling periods were conducted on November 2006 and January 2007., The settlement of shipworm was affected both by tidal level and water movement. Growth was also faster in the low tidal zone lowest in the high tidal zone. Settlement of shipworms was higher in an area where there is rapid water movement (low tidal zone) and low in an area with slow water movement (high tidal zone).